Long time gone - Donlea, Charlie (Kensington Publishing Corp., 2024)
When DNA results reveal a disturbing connection to the mysterious disappearance of a famous baby nearly three decades ago, forensic scientist Dr. Sloan Hastings' increasingly perilous search for answers draws her to an unsettling small Nevada town.